Decoding Consumer Purchase Decisions: The Strategic Role of Digital Marketing, Pricing, and Product Quality - Hudah, Nurhul; sukaris, sukaris (INNOVATION RESEARCH JOURNAL, 2026)
This study aims to analyze the influence of digital marketing, price, and product quality on consumer purchasing decisions. This study employed a quantitative approach with a survey method, distributing questionnaires to frozen food consumers. Purposive sampling was used for sampling, while multiple linear regression was used to analyze the partial and simultaneous effects between variables. Validity and reliability tests were conducted to ensure the quality of the research instrument. The results showed that digital marketing had a significant but negative effect on purchasing decisions, while price had no significant effect. Conversely, product quality was shown to have a positive and significant effect and was the dominant factor in increasing purchasing decisions. Simultaneously, digital marketing, price, and product quality significantly influenced purchasing decisions. The conclusion of this study confirms that product quality is a key determinant of consumer purchasing behavior, while digital marketing strategies need to be optimized for greater effectiveness. Theoretically, this research adds to the literature on consumer behavior by emphasizing the importance of value creation through product quality. Practically, companies are advised to prioritize product quality improvements and evaluate digital marketing strategies to increase market competitiveness.